Times out of Joint: A Glance at Hamlet in Elsinore 1816 - 2016 - Refskou, Anne Sophie (Peripeti, 2025)
2016 was the year the world celebrated the 400th anniversary of the death of William Shakespeare. On 23 April – the day of the Bard’s supposed birth and death – great celebrations with pageantry and parades were mounted on a global scale. Now that 2016 has expired, it may be worth re-remembering the Bard’s birthday party. Not for the slightly excessive pageantry, but for the ways in which the Shakespearean world stage, yet again, demonstrated its ability to inspire critical and timely reflection that day.